Association between remnant cholesterol and arterial stiffness in a Chinese community-based population: A cross-sectional study - Liu, Jiahui; Fan, Fangfang; Liu, Bo; Li, Kaiyin; Jiang, Yimeng; Jia, Jia; Chen, Chuyun; Zheng, Bo; Zhang, Yan (Frontiers in Cardiovascular Medicine, 2022)
Objectives: As a surrogate of arterial stiffness, the brachial-ankle pulse wave velocity (baPWV) is a good predictor of incident cardiovascular disease. Remnant cholesterol (RC) is a proven independent risk factor for cardiovascular disease. However, the relationship between RC and baPWV is unknown. The present study was performed to explore this relationship. Design: Cross-sectional study. Setting and participants: This study involved 8028 participants of a community-based atherosclerosis cohort from China. Community residents aged ≥40 years were enrolled by responding to detailed research recruitment posters or by phone invitation. The participants comprised 2938 (36.60%) men, and their mean age was 56.57 ± 9.04 years. Methods and Results: The baPWV was measured with a standard protocol using the Omron Colin BP-203RPE III device (Omron Healthcare, Kyoto, Japan). RC was calculated as follows: RC = TC − LDL-C − HDL-C. The mean baPWV was 1646.85 ± 374.11 cm/s. The median RC concentration was 0.56 (0.41-0.74) mmol/L. In the multivariate logistic regression analyses, the concentrations of RC, triglycerides (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and non-high-density lipoprotein cholesterol (non-HDL-C) were all positively and independently associated with baPWV. The baPWV was higher in the fourth than first lipid profile quartile. The HDL-C concentration was inversely associated with baPWV. When RC was forced into the model with other lipid profile indices simultaneously, only the RC and TG concentrations remained significantly associated with baPWV. Conclusions: Lipids are independently associated with baPWV. The RC and TG concentrations have stronger associations with arterial stiffness than other lipid indices in the Chinese community-based population.